Projeto "Nexos". Uma instância articuladora entre ensino médio e Universidad Nacional del Litoral - Blesio, Marcel Mónica (Universidad Nacional del Litoral, 2019)
This article reflects on an experience of articulationof levels, which was developed within the frameworkof a Project called Nexos, which was approvedby the University Policies Department of the ArgentineMinistry of Education and Sports and implemented byArticulation and Admission Office, which depends onthe Department of Institutional and Academic Planningof Universidad Nacional del Litoral; and the ProvincialMinistry of Education of Santa Fe. The project wasintended for schools located in the region, in particularthose in the Province of Santa Fe. In this sense,this paper accounts for different actions taken fromMay to December 2018, promoting the articulation between university education and secondary schools,thus encouraging and favoring the access of youth touniversity studies. Also, it was intended to generateinstitutional and curricular conditions which enablegenuine inclusive and permanence processes regardingboth university studies and the continuity of higherstudies through collaborative work among teachers andstudents at both levels.